Thrombotic Microangiopathy Due to Catastrophic Antiphospholipid Antibody Syndrome Confirmed on Skin Biopsy and Treated with Eculizumab. Issue 2 (May 2017) - Hanna, Ramy M.; Hanna, Mina; Larson, Brent; Lopez, Eduardo A.; Wilson, James; Hendifar, Andrew
Introduction: Thrombotic microangiopathies (TMA) can be caused by diverse clinical entities of various etiologies. Thrombotic thrombocytopenic purpura (TTP) is caused by a lack of von Willebrand-factor-cleaving metalloproteinase, ADAMTS13, which is the protein whose deficiency is etiologic in TTP. Shiga-toxin-induced hemolytic uremic syndrome (HUS) differs from atypical HUS (aHUS) due to the presence of the Shiga toxin and enteritis. aHUS is generally seen in younger patients and is linked to genetic and/or acquired complement system dysfunction. In addition to genetic links to the complement system, TMA, TTP, and aHUS have been known to be associated with many acquired triggers, such as malignancy, autoimmune disorders, infections, and pro-thrombotic states. We present the case of an unusual cause of TMA due to catastrophic antiphospholipid antibody syndrome (CAPS). Case Description: An elderly patient with ovarian malignancy had evidence of thrombosis of the 2 lower extremity digits. Since the patient did not have a genetic etiology of complement dysfunction established, this presentation is labeled as a TMA rather than an aHUS. Diagnosis was through a skin biopsy and was treated successfully with complement inhibition by eculizumab, resulting in complete resolution of the pathology, normalization of the platelet count, cessation of hemolysis, and resolution of the acute kidney injury that was attributed to the ongoing TMA. Conclusions: Eculizumab can be useful in treating TMA associated with CAPS in transplant- and nontransplant-related cases, and a skin biopsy may be useful in demonstrating a TMA when the renal biopsy risk/benefit ratio is unfavorable.